Diphenylamine‐Substituted Carbazole‐Based Hole Transporting Materials for Perovskite Solar Cells: Influence of Isomeric Derivatives. (19th January 2018) - Magomedov, Artiom; Paek, Sanghyun; Gratia, Paul; Kasparavicius, Ernestas; Daskeviciene, Maryte; Kamarauskas, Egidijus; Gruodis, Alytis; Jankauskas, Vygintas; Kantminiene, Kristina; Cho, Kyung Taek; Rakstys, Kasparas; Malinauskas, Tadas; et al.
Abstract: A series of new branched hole transporting materials (HTMs) containing two diphenylamine‐substituted carbazole fragments linked by a nonconjugated methylenebenzene unit is synthesized and tested in perovskite solar cells. Synthesis of the investigated materials is performed by a simple two‐step synthetic procedure providing a target product in high yield. The isolated materials demonstrate good thermal stability and majority of the investigated compounds exist in an amorphous state, which is advantageous as there is no risk of crystallization directly in the film. The highest charge drift mobility of µ 0 = 4 × 10 −4 cm 2 V −1 s −1, measured at weak electric fields, is by ca. one order of magnitude higher than that of Spiro‐OMeTAD under identical conditions. From the perovskite solar cell testing results, it can be seen that performance of two new HTMs (V885 andV911 ) is on a par with Spiro‐OMeTAD. Due to the ease of synthesis, good thermal, optical and photophysical properties, this type of molecules hold great promise for practical application in commercial perovskite solar cells. Abstract : Branched hole transporting materials (HTMs), containing two diphenylamine substituted carbazole moieties linked by a nonconjugated fragment, are synthesized and tested in perovskite solar cells. They are synthesized by a simple two‐step synthetic procedure providing target products in high yield. Testing in perovskite solar cells indicates that performance of new HTMs is on a par with Spiro‐OMeTAD.